Atrial fibrillation and COVID-19: an analysis of the ambulatory database - Sizova, Zhanna M.; Zakharova, Valeria L.; Shindryaeva, Natalya N.; Lapidus, Natalia I.; Melnik, Mariya V.; Shikh, Evgenia V.; Grebenshchikova, Ludmila Y.; Beloborodova, Alexandra V.; Polovikov, Ivan P. (Frontiers in Cardiovascular Medicine, 2024)
Atrial fibrillation (AF) is the most common heart rhythm disorder in clinical practice. It worsens the quality of life of patients, leads to an increase in the mortality rate because of its association with a high risk of thromboembolic complications. AF is also associated with a high risk of thromboembolic complications. The current pandemic of a new coronavirus infection, which began in March 2020, was marked by an increase in cardiovascular diseases, including an increase in the number of patients with AF. That is why it is extremely relevant to find answers to questions about the association and mutual influence of AF and coronavirus infection to reduce the risk of vascular complications. However, most research in this area has focused on hospital patients. In this study, an electronic database of outpatients with AF, including patients with a history of COVID-19 infection was analyzed in order to assess the most significant risk factors for complications.